The early reception of manga in the West - Iglesia, Martin de la (Bildnarrative, 2023)
Nowadays, manga are ubiquitous not only in their home country Japan but also in the Western world. In some Western countries, they have even surpassed American and European comics in popularity. When did this manga boom start? Many people would think of the late 1990s, when dubbed anime adaptations of manga such as Dragon Ball or Sailor Moon ran on television. This book, however, explores an earlier wave of manga around the year 1990. It examines what the first translated editions of Kazuo Koike and Gōseki Kojima’s Lone Wolf and Cub and Shōtarō Ishinomori’s Japan Inc. looked like, and how readers in the United States and in Germany reacted towards these manga. Their impact was still rather limited, but then, this first manga wave culminated in 1988/1991 when Katsuhiro Ōtomo’s manga masterpiece, Akira, was published in English and German, among other languages. Its reception in the West is analysed in great depth in this book, including chapters on the perception of Akira as cyberpunk and its anime adaptation. Akira opened the floodgates, and in its wake, many more manga titles found their way to American and European readers, including even lengthy but otherwise mediocre series such as Kazuo Koike and Ryōichi Ikegami’s Crying Freeman, the last of the four manga examined in this book. Although manga sales would later soar to greater heights in the 2000s with One Piece, Naruto and others, the first manga wave of ca. 1987–1995 deserves to be remembered for having paved the way.